A internet e a competência comunicativa na pós-alfabetização - Basso, Cintia Maria (2002)
This work investigates the reading and writing improvement of second grade children from Colégio Centenário – located in Santa Maria, RS, Brazil – using the new technologies (Internet). During the second semester of 2000, the researchers worked with that class developing activities and having to face a challenge: how to use the Internet for the improvement of reading and writing competences of literate children under the Project Work and Educational Action Research perspectives? The methodological conception adopted was the Educational Action Research linked to the Project Work what required a group of researchers so that we could plan and think about the developed actions. The theoretical support of this work comprises readings about the development theories by Piaget and Vygotsky, teachers training, first language acquisition, reading as meaning production, reading and writing as social practices, and the Internet as a mediator of acquisition and transmission of knowledge.